PENGARUH STORE ATMOSPHERE TERHADAP KEPUASAN KONSUMEN PADA AYAM PENYET CINDELARAS BAGAN BATU KABUPATEN ROKAN HILIR - Ema Fitri Lubis; Herman; Tirza Tantri Indira (stiatabalong.ac.id, 2023)
Atmosphere (Store Atmospere) is one of the things that restaurant and cafe owners can do to compete with their competitors, because Store Atmospere can be one of the things that can increase consumer satisfaction when visiting the store. The purpose of this study was to analyze and explain the effect of sotre atmosphere on consumer satisfaction in the Bagan Batu Cinderelas Penyet chicken, Rokan Hilir Regency. The research method used in this study is a quantitative method with a descriptive approach. Respondents in this study were 100 respondents by means of sampling using non-probability methods with incidental sampling techniques. Data collection methods consist of questionnaires, observations and documentation. Data analysis in this study used simple linear regression analysis. The results showed that variable X, namely store atmosphere, was categorized as good, while variable Y, namely customer satisfaction, was also categorized as good. For simple linear regression results show that store atmosphere has a significant relationship to customer satisfaction. It can be concluded that Store Atmosphere has a significant effect on Consumer Satisfaction in Cindelaras Penyet Chicken. Keywords : Store Atmospere, Consumer Satisfaction, Cindelaras Penyet Chicken